Interacted multiple ant colonies optimization approach to enhance the performance of ant colony optimization algorithms - Aljanaby, Alaa; Ku-Mahamud, Ku Ruhana; Md. Norwawi, Norita (Canadian Center of Science and Education, 2010)
One direction of ant colony optimization researches is dividing the ants’ population into several colonies. These colonies work together to collectively solve an optimization problem. This approach offers good opportunity to explore a large area of the search space. This paper proposes a new generic algorithmic approach that utilized multiple ant colonies with several new interaction techniques. Computational test shows promising results of the new approach. The proposed approach outperforms the single colony ant algorithms in term of solution quality with the same computational effort.